2014
DOI: 10.3233/jad-141149
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Plasma Protein Classifier to Identify Alzheimer's Disease

Abstract: Biomarkers currently used in the aid for the diagnosis of Alzheimer's disease (AD) are cerebrospinal fluid (CSF) protein markers and brain neuroimaging markers. These biomarkers, however, either involve semi-invasive procedures or are costly to measure. Thus, AD biomarkers from more easily accessible body fluids, such as plasma, are very enticing. Using an aptamer-based proteomic technology, we profiled 1,129 plasma proteins of AD patients and non-demented control individuals. A 5-protein classifier for AD ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 76 publications
0
25
0
1
Order By: Relevance
“…Recently, 2 candidate signatures of progression to AD were proposed. 50,51 These studies were, however, limited to the prediction of progression to AD 1 year before its clinical diagnosis. In addition to plasma biomarkers, CSF-based biomarkers may be particularly representative of the disease progression because CSF is in close contact with the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 candidate signatures of progression to AD were proposed. 50,51 These studies were, however, limited to the prediction of progression to AD 1 year before its clinical diagnosis. In addition to plasma biomarkers, CSF-based biomarkers may be particularly representative of the disease progression because CSF is in close contact with the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…A newly developed SOMAscan discovery-based platform was used to analyze 1129 plasma proteins simultaneously in blood samples from patients with AD and healthy controls [247]. In the discovery set, a 5-protein classifier (S100A9, CD84, CD226, AIF1, and ESAM) was identified that discriminated people with AD from healthy controls with a sensitivity and specificity of 90.0% and 84.2%, respectively, outperforming CSF tau and Aβ 42 markers from the same cases.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…In the discovery set, a 5-protein classifier (S100A9, CD84, CD226, AIF1, and ESAM) was identified that discriminated people with AD from healthy controls with a sensitivity and specificity of 90.0% and 84.2%, respectively, outperforming CSF tau and Aβ 42 markers from the same cases. In a validation study, the classifier discriminated controls from individuals with MCI with 96.7% sensitivity and 80% specificity [247]. Finally, an unbiased mass spectrometric lipidomics approach was used to identify a plasma phospholipid panel that predicted phenoconversion to MCI or AD within a 2 to 3-year timeframe with > 90% accuracy [248].…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…These techniques require either invasive lumbar punctures or expensive PET analyses, which rely on the use of radioactive compounds. Thus, there is a general agreement that a minimal-invasive, reliable, and cost-effective blood test is requested as a first screening funnel to identify individuals with high risk for AD [11][12][13][14][15]. To date, only few blood tests present the potential to detect AD [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%